Na pragu - Valič, Urša (Etnolog. Nova vrsta (Ljubljana), 2010)
The article addresses the social exclusion of handicapped/disabled women. Its first part provides a survey of the socio-cultural exclusion of handicapped/disabled women, and its second part describes aspects of social exclusion in the cases of sex, pregnancy, birth giving and motherhood.
Keywords: woman; ženske; invalidnost; hendikep; spolna identiteta; materinstvo; družbena izključenost